2014
DOI: 10.3109/0886022x.2014.900600
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic elevation of creatine kinase in patients with hyponatremia

Abstract: Thirty-two patients with hyponatremia and hyper-CKemia were identified. All patients had no muscular symptoms or weakness. The commonest cause of hyponatremia in this cohort was related to diuretics (50%). The mean sodium level on presentation was 116.0 ± 6.9 mmol/L and the median peak CK was 895.5 (interquartile range: 610.8-1691.8) IU/L. Six (18%) patients developed acute kidney injury (AKI). The length of hospital admission of the entire cohort was 8.0 ± 5.8 days. Patients with hyper-CKemia in the setting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…No causal association has been established between desmopressin acetate‐induced hyponatremia and muscle injury in animal studies 19 . In a clinical study, asymptomatic hyperCKemia was associated with hyponatremia caused by diuretics and polydipsia, which may have been complicated by AKI 20 . Compared to ultra‐athletes with normonatremia, exercise‐associated hyponatremia is prone to develop into exercise‐associated RM 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No causal association has been established between desmopressin acetate‐induced hyponatremia and muscle injury in animal studies 19 . In a clinical study, asymptomatic hyperCKemia was associated with hyponatremia caused by diuretics and polydipsia, which may have been complicated by AKI 20 . Compared to ultra‐athletes with normonatremia, exercise‐associated hyponatremia is prone to develop into exercise‐associated RM 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 19 In a clinical study, asymptomatic hyperCKemia was associated with hyponatremia caused by diuretics and polydipsia, which may have been complicated by AKI. 20 Compared to ultra‐athletes with normonatremia, exercise‐associated hyponatremia is prone to develop into exercise‐associated RM. 21 Severe hyponatremia was observed in patient 4, and we considered that hyponatremia might promote the development of hyperCKemia.…”
Section: Discussionmentioning
confidence: 99%
“…Comparably, hyponatremia overcorrection has been known to cause rhabdomyolysis as indicated by elevated CPK and/or renal failure [ 12 ]. This degree of elevation can vary generally from the hundreds to the low thousands.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia is reported to cause myocyte destruction and the leakage of troponin, CK-MB, and LDH from the damaged membranes into the circulation. 23 Hypokalemia-induced myopathy and massive CK elevation as the first presentation of Conn’s syndrome may occur due to hypertension. 24 Zhang et al 9 in 2004 reported that the administration of glucose-insulin-K combination attenuated the accumulation of LDH and CK in rabbits subjected to myocardial injuries.…”
Section: Discussionmentioning
confidence: 99%